Edukasi Cuci Tangan Pakai Sabun & Pemasangan Sarana Cuci Tangan Percontohan di SDN 7 Gedong Tataan Pesawaran Lampung - Tati Baina Gultom; Agus Sutopo; Haris Kadarusman (Jurnal Informasi Pengabdian Masyarakat, 2026)
Indonesian government is implementing the Free Nutritional Meal Program (MBG) in all schools in Indonesia. Washing hands with soap and running water (CTPS) is one of the keys to the success of the MBG program. Eating without clean hands can cause germs to enter, causing diseases such as diarrhea, digestive disorders and reducing the nutritional benefits of food, can even cause poisoning, so that CTPS before eating is an absolute requirement for health and the sustainability of the program. The objective of this activity is to educate students on proper handwashing with soap and running water (CTPS) as well as clean and healthy living practices (PHBS) at school, and to ensure the availability of adequate facilities and infrastructure for handwashing with soap and running water (CTPS) at SDN 7 Gedong Tataan, Pesawaran Regency, Lampung Province. The activity method uses a combination of counseling, demonstrations and direct practice. The results of this activity are increased knowledge among all students about handwashing with soap and running water (CTPS) and clean and healthy living behaviors (PHBS) at school as well as the installation of 3 (three) units of handwashing facilities at SDN 7 Gedong Tataan, Pesawaran Regency, Lampung Province. The students are enthusiastic and eager to practice directly the steps of handwashing with soap and running water (CTPS) and using the installed CTPS facilities. Overall, this activity had a positive impact on students of SDN 7 Gedong Tataan, Pesawaran Regency, Lampung Province.